Production process of rubber material for bearing sealing element

By using a combination of modified hydrotalcite and silane coupling agent in rubber seals, combined with the mixing vulcanization process of nitrile rubber and other additives, the mechanical properties and oil resistance of rubber seals in high temperature and high pressure environments are solved. It achieves excellent mechanical properties and oil resistance, suitable for sealing applications of automotive engine components.

CN119241928APending Publication Date: 2025-01-03TAI ZHOU JIA XIAN QI CHE LING BU JIAN ZHI ZAO YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411344667.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-03

Smart Images

  • Figure BDA0005060628350000081
    Figure BDA0005060628350000081
  • Figure BDA0005060628350000091
    Figure BDA0005060628350000091
Patent Text Reader

Abstract

The invention discloses a production process of a rubber material for a bearing sealing element, and belongs to the technical field of rubber materials, and the production process comprises the following steps: S1, adding hydrotalcite into an ethanol aqueous solution, carrying out ultrasonic dispersion to obtain a hydrotalcite dispersion liquid, adding a modified silane coupling agent at 80-85 DEG C, and carrying out stirring reflux, cooling, suction filtration, washing and drying to obtain a rubber material; grinding to obtain modified hydrotalcite; s2, mixing nitrile rubber, then adding carbon black, modified hydrotalcite, itaconic acid, zinc oxide, stearic acid, a vulcanizing agent, a plasticizer and an accelerant, continuously mixing, discharging, and tabletting to obtain a rubber sheet; s3, the rubber sheet is cooled and then subjected to vulcanization treatment, and the rubber material is obtained. The obtained rubber material has excellent mechanical properties and oil resistance, and is simple in production process, economical in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber materials, and in particular relates to a production process of rubber materials for bearing seals. Background Art

[0002] A rubber seal is an annular cover consisting of one or more parts. It is fixed to one bearing ring or washer and contacts or forms a narrow labyrinthine gap with the other ring or washer, preventing lubricant leakage and foreign objects from entering. With the rapid development of the automotive industry, the demand for rubber seals used in components such as cylinders and pistons in automotive engines is increasing. Rubber seals used in cylinders and pistons in automotive engines must not only provide a barrier seal, but also, because the medium they seal is fuel or lubricating oil, they must also be oil-resistant, high-temperature resistant, and have good elasticity.

[0003] With the continuous advancement of technology, the environments in which rubber seals are used are increasingly subject to factors such as high temperature, high pressure, and humidity. These environments can cause rubber seals to become loose, age, become brittle, and fatigue, resulting in their mechanical properties failing to meet actual production requirements. Once the seal fails, it can affect the normal operation of the equipment. In the prior art, rubber seals are primarily made of materials including nitrile rubber, fluororubber, or chloroprene rubber. Fluororubber offers excellent chemical resistance, antioxidant properties, high temperature tolerance, and wear resistance, but is relatively expensive. Neoprene has exceptional weather and heat resistance, maintaining stable physical and mechanical properties within a temperature range of 40-120°C, but has poor oil resistance. Nitrile rubber, while characterized by its high temperature resistance, oil resistance, wear resistance, aging resistance, and excellent sealing properties, is currently the most widely used and lowest-cost rubber seal when used in media such as gasoline and silicone lubricants. However, it also suffers from drawbacks such as poor elasticity and UV resistance.

[0004] Therefore, it is of great significance to provide a rubber seal that is not only oil-resistant and aging-resistant but also elastic and UV-resistant. Summary of the Invention

[0005] The object of the present invention is to provide a production process of a rubber material for a bearing seal, so as to solve the problem of poor oil resistance of the rubber material in the prior art.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A production process for a rubber material for a bearing seal comprises the following steps:

[0008] S1. Adding hydrotalcite to an ethanol aqueous solution and dispersing it by ultrasonication to obtain a hydrotalcite dispersion; adding a modified silane coupling agent at 80-85° C.; stirring and refluxing; cooling; filtering; washing; drying; and grinding to obtain a modified hydrotalcite;

[0009] S2, mixing the nitrile rubber, then adding carbon black, modified hydrotalcite, itaconic acid, zinc oxide, stearic acid, vulcanizing agent, plasticizer and accelerator to continue mixing, discharging, and sheeting to obtain a film;

[0010] S3. After the film is cooled, it is vulcanized to obtain a rubber material.

[0011] As a further embodiment of the present invention, the usage ratio of hydrotalcite, ethanol aqueous solution and modified silane coupling agent in S1 is 1.5-1.6 g: 25 mL: 0.25-0.30 mL.

[0012] As a further embodiment of the present invention, the modified silane coupling agent is prepared by the following steps:

[0013] N-phenyl-1,4-phenylenediamine and silane coupling agent KH-560 were mixed, stirred and refluxed at 135-140° C. for 3-3.5 hours, and cooled to obtain a modified silane coupling agent.

[0014] As a further embodiment of the present invention, the usage ratio of N-phenyl-1,4-phenylenediamine and silane coupling agent KH-560 is 1.8-2 g:10-10.5 mL.

[0015] As a further embodiment of the present invention, the weight ratio of nitrile rubber, carbon black, modified hydrotalcite, itaconic acid, zinc oxide, stearic acid, vulcanizing agent, plasticizer and accelerator is 100:20-25:5-10:10-15:3-5:1-2:1.5-3:25-30:1.5-3.

[0016] As a further embodiment of the present invention, the vulcanizing agent is dicumyl peroxide.

[0017] As a further embodiment of the present invention, the plasticizer is one of dioctyl phthalate and dibutyl phthalate.

[0018] As a further embodiment of the present invention, the accelerator is at least one of accelerator TMTD, accelerator MBTS, accelerator MBT, and accelerator CBS.

[0019] As a further solution of the present invention, the vulcanization temperature during the vulcanization treatment in S3 is 150-200° C., and the vulcanization time is 15-25 minutes.

[0020] Beneficial effects of the present invention:

[0021] The present invention provides a production process for a rubber material for a bearing seal. The process comprises kneading nitrile rubber, then adding carbon black, modified hydrotalcite, itaconic acid, zinc oxide, stearic acid, a vulcanizing agent, a plasticizer, and an accelerator, and continuing to knead the mixture. The mixture is discharged, sheeted, and then vulcanized after cooling to obtain a rubber material. The obtained rubber material has excellent mechanical properties and oil resistance, and the production process is simple, cost-effective, and suitable for large-scale production.

[0022] The present invention firstly allows the primary amine group of N-phenyl-1,4-phenylenediamine, an antioxidant intermediate with good reactivity, to undergo a ring-opening reaction with the epoxy group of the silane coupling agent KH-560 to prepare an amino group-containing coupling agent with antioxidant performance. The coupling agent is then subjected to a chemical grafting reaction with the hydroxyl structure between the layers and on the surface of the hydrotalcite to synthesize a hydrotalcite material with antioxidant functionality. Simultaneously, the dispersion performance of the hydrotalcite and the macromolecular antioxidant in rubber is improved, thereby further improving the mechanical properties and antioxidant performance of the rubber material.

[0023] Furthermore, itaconic acid is added during the preparation process. Itaconic acid contains C=C double bonds, which, when triggered by a vulcanizing agent, can form free radicals that crosslink with rubber chains, resulting in grafting onto the rubber chains. As the crosslink density of the rubber increases, the intermolecular forces between the rubber molecules increase, and the free volume within the network decreases, making it difficult for oils to diffuse, thereby significantly improving the rubber's oil resistance. Furthermore, the carboxyl groups in the unsaturated carboxylic acid can form coordination bonds with the metal ions in the hydrotalcite and hydrogen bonds with the hydroxyl groups, effectively enhancing the interaction between the hydrotalcite and the nitrile rubber, significantly improving the dispersibility of the hydrotalcite in the nitrile rubber. Furthermore, itaconic acid and ZnO react at high temperatures to form zinc itaconate, a metal salt of an unsaturated carboxylic acid. Zinc itaconate can significantly improve the mechanical properties of the rubber material, enabling it to achieve a high elongation at break while maintaining a high hardness, resulting in a high elasticity. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0025] Example 1

[0026] This embodiment provides a production process for a rubber material for a bearing seal, comprising the following steps:

[0027] S1. Add 1.5 g of hydrotalcite to 25 mL of 95 wt% ethanol aqueous solution and ultrasonically disperse for 30 min to obtain a hydrotalcite dispersion. Add 0.25 mL of a modified silane coupling agent at 85° C., stir and reflux, cool, filter, wash with anhydrous ethanol five times, dry, and grind to obtain a modified hydrotalcite.

[0028] S2. Weigh 100 parts of nitrile rubber by weight, then add 20 parts of carbon black, 5 parts of modified hydrotalcite, 10 parts of itaconic acid, 3 parts of zinc oxide, 1 part of stearic acid, 1.5 parts of dicumyl peroxide, 25 parts of dioctyl phthalate and 1.5 parts of accelerator TMTD, continue mixing, discharge, and sheet to obtain a film;

[0029] S3. After the film is cooled, it is vulcanized at a temperature of 150° C. for 15 minutes to obtain a rubber material.

[0030] The modified silane coupling agent is prepared by the following steps:

[0031] 1.8 g of N-phenyl-1,4-phenylenediamine and 10 mL of silane coupling agent KH-560 were mixed, stirred and refluxed at 135° C. for 3 h, and cooled to obtain a modified silane coupling agent.

[0032] Example 2

[0033] Compared with Example 1, the only difference is:

[0034] S1. Add 1.55 g of hydrotalcite to 25 mL of 95 wt% ethanol aqueous solution and ultrasonically disperse for 30 min to obtain a hydrotalcite dispersion. Add 0.25 mL of a modified silane coupling agent at 85° C., stir and reflux, cool, filter, wash five times with anhydrous ethanol, dry, and grind to obtain a modified hydrotalcite.

[0035] Example 3

[0036] Compared with Example 1, the only difference is:

[0037] S1. Add 1.6 g of hydrotalcite to 25 mL of 95 wt% ethanol aqueous solution and ultrasonically disperse for 30 min to obtain a hydrotalcite dispersion. Add 0.30 mL of a modified silane coupling agent at 85° C., stir and reflux, cool, filter, wash five times with anhydrous ethanol, dry, and grind to obtain a modified hydrotalcite.

[0038] Example 4

[0039] Compared with Example 1, the only difference is:

[0040] The modified silane coupling agent is prepared by the following steps:

[0041] 2 g of N-phenyl-1,4-phenylenediamine and 10.5 mL of silane coupling agent KH-560 were mixed, stirred and refluxed at 135° C. for 3 h, and cooled to obtain a modified silane coupling agent.

[0042] Example 5

[0043] Compared with Example 1, the only difference is:

[0044] S2. Weigh 100 parts of nitrile rubber by weight, then add 20 parts of carbon black, 7 parts of modified hydrotalcite, 10 parts of itaconic acid, 3 parts of zinc oxide, 1 part of stearic acid, 1.5 parts of dicumyl peroxide, 25 parts of dioctyl phthalate and 1.5 parts of accelerator TMTD, continue mixing, discharge the material, and press into sheets to obtain a film.

[0045] Example 6

[0046] Compared with Example 1, the only difference is:

[0047] S2. Weigh 100 parts of nitrile rubber by weight, then add 20 parts of carbon black, 10 parts of modified hydrotalcite, 10 parts of itaconic acid, 3 parts of zinc oxide, 1 part of stearic acid, 1.5 parts of dicumyl peroxide, 25 parts of dioctyl phthalate and 1.5 parts of accelerator TMTD, continue mixing, discharge the material, and press into sheets to obtain a film.

[0048] Example 7

[0049] Compared with Example 1, the only difference is:

[0050] S3. After the film is cooled, it is vulcanized at a temperature of 180° C. for 20 minutes to obtain a rubber material.

[0051] Comparative Example 1

[0052] This comparative example provides a production process for a rubber material for a bearing seal, comprising the following steps:

[0053] S1. Weigh 100 parts of nitrile rubber by weight, then add 20 parts of carbon black, 5 parts of hydrotalcite, 10 parts of itaconic acid, 3 parts of zinc oxide, 1 part of stearic acid, 1.5 parts of dicumyl peroxide, 25 parts of dioctyl phthalate and 1.5 parts of accelerator TMTD, continue mixing, discharge, and press to obtain a film;

[0054] S2. After the film is cooled, it is vulcanized at a temperature of 150° C. for 15 minutes to obtain a rubber material.

[0055] Comparative Example 2

[0056] This comparative example provides a production process for a rubber material for a bearing seal, comprising the following steps:

[0057] S1. Add 1.5 g of hydrotalcite to 25 mL of 95 wt% ethanol aqueous solution and ultrasonically disperse for 30 min to obtain a hydrotalcite dispersion. Add 0.25 mL of a modified silane coupling agent at 85° C., stir and reflux, cool, filter, wash with anhydrous ethanol five times, dry, and grind to obtain a modified hydrotalcite.

[0058] S2. Weigh 100 parts of nitrile rubber by weight, mix them, then add 20 parts of carbon black, 5 parts of modified hydrotalcite, 3 parts of zinc oxide, 1 part of stearic acid, 1.5 parts of dicumyl peroxide, 25 parts of dioctyl phthalate and 1.5 parts of accelerator TMTD, continue mixing, discharge the materials, and press them into sheets to obtain a film;

[0059] S3. After the film is cooled, it is vulcanized at a temperature of 150° C. for 15 minutes to obtain a rubber material.

[0060] Comparative Example 3

[0061] Compared with Example 1, the only difference is:

[0062] S1. Add 1.35 g of hydrotalcite to 25 mL of 95 wt% ethanol aqueous solution and ultrasonically disperse for 30 min to obtain a hydrotalcite dispersion. Add 0.25 mL of a modified silane coupling agent at 85° C., stir and reflux, cool, filter, wash five times with anhydrous ethanol, dry, and grind to obtain a modified hydrotalcite.

[0063] Comparative Example 4

[0064] Compared with Example 1, the only difference is:

[0065] S1. Add 1.75 g of hydrotalcite to 25 mL of ethanol aqueous solution (95 wt%) and ultrasonically disperse for 30 min to obtain a hydrotalcite dispersion. Add 0.25 mL of a modified silane coupling agent at 85°C, stir and reflux, cool, filter, wash with anhydrous ethanol 5 times, dry, and grind to obtain a modified hydrotalcite.

[0066] Comparative Example 5

[0067] Compared with Example 1, the only difference is:

[0068] The 5 parts of modified hydrotalcite in Example 1 were replaced by 3 parts of modified hydrotalcite.

[0069] Comparative Example 6

[0070] Compared with Example 1, the only difference is:

[0071] The 5 parts of modified hydrotalcite in Example 1 were replaced by 13 parts of modified hydrotalcite.

[0072] Comparative Example 7

[0073] Compared with Example 1, the only difference is:

[0074] S2. Weigh 100 parts of nitrile rubber by weight, then add 20 parts of carbon black, 5 parts of modified hydrotalcite, 3 parts of zinc oxide, 1 part of stearic acid, 1.5 parts of dicumyl peroxide, 25 parts of dioctyl phthalate and 1.5 parts of accelerator TMTD and continue mixing, discharge the material, and press into sheets to obtain a film.

[0075] Comparative Example 8

[0076] Compared with Example 1, the only difference is:

[0077] S2. Weigh 100 parts of nitrile rubber by weight, then add 15 parts of carbon black, 5 parts of modified hydrotalcite, 8 parts of itaconic acid, 3 parts of zinc oxide, 1 part of stearic acid, 1.5 parts of dicumyl peroxide, 25 parts of dioctyl phthalate and 1.5 parts of accelerator TMTD, continue mixing, discharge, and press to obtain a film.

[0078] Comparative Example 9

[0079] Compared with Example 1, the only difference is:

[0080] S2. Weigh 100 parts of nitrile rubber by weight, then add 20 parts of carbon black, 3 parts of modified hydrotalcite, 18 parts of itaconic acid, 1 part of zinc oxide, 1 part of stearic acid, 1.5 parts of dicumyl peroxide, 25 parts of dioctyl phthalate and 1.5 parts of accelerator TMTD, continue mixing, discharge the material, and press into sheets to obtain a film.

[0081] Comparative Example 10

[0082] Compared with Example 1, the only difference is:

[0083] S3. After the film is cooled, it is vulcanized at a temperature of 135° C. for 15 minutes to obtain a rubber material.

[0084] The following performance tests were performed on Examples 1 to 7 and Comparative Examples 1 to 10:

[0085] 1) Tensile strength and tensile elongation: tested according to ASTM D412 (temperature: 23°C);

[0086] 2) Tear resistance: Tear resistance test is carried out in accordance with GB / T 529-1999 standard;

[0087] 3) Oil resistance: Oil resistance test is carried out in accordance with ASTM D471 standard.

[0088] The test results are shown in Table 1:

[0089] Table 1

[0090]

[0091]

[0092] As can be seen from Table 1, the tensile strength, tear strength, and oil resistance of the rubber materials obtained in Comparative Examples 1-10 are all inferior to those of Examples 1-7. This demonstrates that the rubber material for bearing seals provided by the present invention has excellent mechanical properties and oil resistance, broadening the application scenarios of rubber seals.

[0093] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0094] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A production process of a rubber material for a bearing seal, characterized in that: The following steps are involved: S1, adding hydrotalcite to an ethanol aqueous solution, ultrasonically dispersing to obtain a hydrotalcite dispersion, adding a modified silane coupling agent at 80-85° C., stirring and refluxing, cooling, filtering, washing, drying, and grinding to obtain a modified hydrotalcite; S2, mixing the nitrile rubber, then adding carbon black, modified hydrotalcite, itaconic acid, zinc oxide, stearic acid, vulcanizing agent, plasticizer and accelerator to continue mixing, discharging, and pressing to obtain a film; S3, after the film is cooled, vulcanization treatment is performed to obtain a rubber material.

2. The production process of a rubber material for a bearing seal according to claim 1, characterized in that: The dosage ratio of hydrotalcite, ethanol aqueous solution and modified silane coupling agent in S1 is 1.5-1.6 g: 25 mL: 0.25-0.30 mL.

3. The production process of a rubber material for a bearing seal according to claim 1, characterized in that: The modified silane coupling agent is prepared by the following steps: N-phenyl-1,4-phenylenediamine and silane coupling agent KH-560 are mixed, stirred and refluxed at 135-140° C. for 3-3.5 hours, and cooled to obtain a modified silane coupling agent.

4. The production process of a rubber material for a bearing seal according to claim 3, characterized in that: The dosage ratio of N-phenyl-1,4-phenylenediamine and silane coupling agent KH-560 is 1.8-2g:10-10.5mL.

5. The production process of a rubber material for a bearing seal according to claim 1, characterized in that: The weight ratio of nitrile rubber, carbon black, modified hydrotalcite, itaconic acid, zinc oxide, stearic acid, vulcanizer, plasticizer and accelerator is 100:20-25:5-10:10-15:3-5:1-2:1.5-3:25-30:1.5-3.

6. The production process of a rubber material for a bearing seal according to claim 1, characterized in that: The vulcanizing agent is dicumyl peroxide.

7. The production process of a rubber material for a bearing seal according to claim 1, characterized in that: The plasticizer is one of dioctyl phthalate and dibutyl phthalate.

8. The production process of a rubber material for a bearing seal according to claim 1, characterized in that: The accelerator is at least one of accelerator TMTD, accelerator MBTS, accelerator MBT and accelerator CBS.

9. The production process of a rubber material for a bearing seal according to claim 1, characterized in that: During the vulcanization treatment in S3, the vulcanization temperature is 150-200°C and the vulcanization time is 15-25 minutes.